Social-Mapping Sebagai Landasan Perencanaan Pemberdayaan Masyarakat Berkelanjutan - Sukaris, Sukaris (Universitas Muhammadiyah Gresik, 2019)
Planning a community empowerment should be placed as a reference of how to implement development programs and empowerment in order to comply with the direction and expectations of society. Planning community development is often called social mapping. Social mapping is mean to see and know the state of society, and then do a need assessment. The purpose of research is to identify problems of socio-economic, socio-economic potential and other opportunities that can be developed, the characteristics of the targeted empowerment. And to identify the type and level of need empowerment programs that enhance self-sufficiency. This research approach uses a qualitative approach case study. Results show focuses on the socio-economic problems of the most visible problems and are at locations surrounding environment companies ranging from the causes and impact. The various socio-economic potentials focuses on the dimensions of the current potential, institutional cooperation and continued development. The characteristics of the targeted community empowerment have noticed about those directly affected, to develop local potential, capacity building, sustainable programs, provide added value and synergy with the government. That the identification program carried out within a specified period in accordance with the strategic plan and business plan and based on performance and public expectations